Undernutrition among School Going Children of Shirur Village, Bagalkot: A Cross-Sectional Study - Kalasker, Pavan S; Anjum, Waseem; Kurre, Bhaskar (National Journal of Community Medicine, 2016)
Introduction: Undernutrition among children accounts for more than half of child morbidity and mortality. Undernourished children are at risk of growth retardation, reduced learning capacity and impaired motor & cognitive development. Objectives: This study was conducted to find the prevalence of underweight among school going children of Shirur village and to find the socio-demographic risk factors associated with underweight. Methodology: A cross-sectional study was conducted among 1308 school going children in Shirur village a rural field practice area of S N Medical College Bagalkot. Students were interviewed with help of oral questionnaire containing socio-demographic details followed by anthropometric measurements. WHO growth charts 2007 were used for comparison to find prevalence of underweight and stunting. Results: Prevalence of overall underweight and stunting was 35% and 25.7% respectively. Underweight was significantly high among females, 6-10 year age group, primary class, Hindu religion, family size of more than or equal to six members and maternal literacy. Conclusion: This study reflects the high prevalence of underweight and stunting among school going children in rural areas. Improvement of maternal literacy, family planning and nutrition education will reduce the undernutriton in long run. Urgent nutritional interventions by both public and private sector especially in rural areas is the need of hour.